Toward a Recognition System for Mexican Sign Language: Arm Movement Detection - Gabriela Hilario-Acuapan; Keny Ordaz-Hernández; Mario Castelán; Ismael Lopez-Juarez (Sensors)
This paper describes ongoing work surrounding the creation of a recognition system for Mexican Sign Language (LSM). We propose a general sign decomposition that is divided into three parts, i.e., hand configuration (HC), arm movement (AM), and non-hand gestures (NHGs). This paper focuses on the AM features and reports the approach created to analyze visual patterns in arm joint movements (wrists, shoulders, and elbows). For this research, a proprietary dataset—one that does not limit the recognition of arm movements—was developed, with active participation from the deaf community and LSM experts. We analyzed two case studies involving three sign subsets. For each sign, the pose was extracted to generate shapes of the joint paths during the arm movements and fed to a CNN classifier. YOLOv8 was used for pose estimation and visual pattern classification purposes. The proposed approach, based on pose estimation, shows promising results for constructing CNN models to classify a wide range of signs.